O processo de formulação estratégica em pequenas empresas - Silva, Giselle Moraes e (2006)
Results from a search on small firms are provided. Its purpose has been to identify the process of strategy formulations based on theories by Mintzberg and, where possible, possible specificities in these organizations. The owners/directors of five small firms were interviewed. They were consciously selected which resulted in a multiple case study. The owner/director is practically always accountable for the firm's strategy formulation, coupled to other activities within the organization management. Frequently the owner/director fails to have a clear idea of the next steps to take. These are taken non-systemically and without the use of the basic concepts of strategic formulations. Information on the environment is rare and some owners/directors perceive changes in their sectors when these are already being processed. Although specificities and certain particulars have been detected in the studied firms, as found in the literature, some are already involved in change.